Hierarchical control of heart-assist devices. - Boston, J.R (IEEE Robotics and automation magazine)
The demand for transplantable hearts exceeds the supply, and transplant candidates often wait long periods before a suitable donor organ becomes available. When pharmacological treatment fails to maintain adequate blood circulation, mechanical assistance of one or both ventricles is the only available therapy other than transplantation. This article describes the development of control techniques for ventricular-assist devices and a hierarchical control structure to regulate the operation of a turbo-hydrodynamic assist device.